Characteristics of Marginal Groups - Herawati, Sri Erni; Febriani, Fani (Journal Social Civilecial, 2023)
This article discusses marginal groups that are identical with marginalized small communities. Characteristics of marginalized groups that do not have a clear / permanent livelihood. And their lives depend on the existing situation and conditions. Or have a steady livelihood but the income they get is below the standard of living needs. This can be seen from several perspectives, namely in terms of health, social economy and others.